Understanding the Effects and Impacts of Counter-Terrorist Financing Policy and Practice - Davis, Jessica (Terrorism and political violence, 2024)
After twenty years of global counterterrorist financing (CTF) policy and practice, there is little consensus on what these have achieved, and little empirical evidence to determine if, or how, CTF works to reduce the financing of terrorism or terrorism more broadly. In many cases, the lack of clarity on these issues is due to poor articulation of the specific approaches to countering the financing of terrorism (CTF). The main approaches considered in the literature are the criminalization of terrorist financing and the financial exclusion (sanctions) approach, but there are many other identifiable policy approaches to CTF. In order to clarify our understanding of CTF, I examined over 550 pieces of scholarly literature covering both terrorist financing and CTF to develop a typology of seven main approaches to CTF, some of which have been studied and evaluated far more than others, but all of which are part of the “bucket” of policy options available to states. These different CTF approaches need to be considered and evaluated individually in order to design better policies and practices.